Analisis Return of Asset (ROA) dan Return of Equity (ROE) pada Perusahaan Transportasi PT. Blue Bird - Muarif Leo; Herman Herman (Politeknik Baubau, 2022)
This study aims 1) To determine the return on assets (ROA) obtained by the company PT. Blue Bird, 2) To interpret the return on assets (ROA) obtained by the company PT. Blue Bird, 3) To find out the return of equity (ROE) obtained by the company PT. Blue Bird, 4) To interpret the return of equity (ROE) obtained by the company PT. Blue Bird. The results of this study indicate that the company's profit of PT Blue Bird reached more than four hundred billion in 2018, but in the following year until 2020 the net profit generated by the company is decreasing even in 2019 the company suffered a very large loss, which touched the number more than one hundred and sixty billion, this is due to a pandemic experienced by the world so that it has an impact on company income, especially in the transportation sector, this is also due to regulations achieved by the government to prevent the spread of the corona virus by prohibiting people from traveling so that it will certainly greatly impacted the income of businesses in the transportation sector such as PT Blue Bird.